Spatial and temporal changes of vegetation cover in karbala using vegetation index difference - Alsamee, Lamyaa Abed Taha Al- Edhari, Mahmood Badir (International Journal of Aquatic Research and Environmental Studies, 2025)
The research aims to calculate the spatial and temporal changes in the study area, where the analysis of satellite images from the Moon (Land Sat) that were taken for the years (1993, 2008, 2023) was relied upon. It is noted that the area of vegetation cover was in 1993 about (971.05) km2, while the area of vegetation cover in 2008 became about (1012.6) km2, but in 2023 it became about (1422.64) km2. The research problem emerged what trends of change in the area of vegetation cover in the holy province of Karbala, spatially and temporally using RS. By comparing the area of vegetation cover in the period, we find that the area of variable vegetation cover is equal to 41 km2. The area of vegetation increased in 2023, where it became 1422 km2, where the area of agricultural land was 951 km2, constituting a percentage of 67%, while the area of natural plant was 471 km2, constituting a percentage of 33%, which means that there is a positive change of an area of about 480 km2, that is, the area of agricultural land is increasing, while the area of natural plant is decreasing 230 km2. The beginning was with the spread of modern agriculture in the Karbala Plateau, but at a slow pace at the beginning. In 2010, the signs of success appeared on the experience. Quick and serious steps began to take advantage of these areas of neglected desert land. It seems that modern agriculture using axial sprinklers was the main step in success until it reached its peak at the end of 2023, and the total area became about 1031.43 km2. The use of remote sensing techniques is an important means of extracting sensitive and accurate information about the characteristics of any target on the surface of the earth and the emergency changes that occur to that target, as well as determining the extent of vegetation cover change in the research area caused by a variety of natural and human factors.